2018
DOI: 10.1371/journal.pbio.2004404
|View full text |Cite
|
Sign up to set email alerts
|

Hair cell identity establishes labeled lines of directional mechanosensation

Abstract: Directional mechanoreception by hair cells is transmitted to the brain via afferent neurons to enable postural control and rheotaxis. Neuronal tuning to individual directions of mechanical flow occurs when each peripheral axon selectively synapses with multiple hair cells of identical planar polarization. How such mechanosensory labeled lines are established and maintained remains unsolved. Here, we use the zebrafish lateral line to reveal that asymmetric activity of the transcription factor Emx2 diversifies h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…To test lateral-line somatotopy functionally, we used a combination of pLAN map rewiring and a rheotaxis assay. In previous studies, we found that after peripheral nerve transection LANs regenerate axons to re-innervate neuromasts within 36 h 18,44 . Regenerating axons reproduce synapses with hair cells of the original planar polarization, recapitulating neuronal directional tuning 18,44 .…”
Section: Central-arbor Structure and Plan Receptive Fieldmentioning
confidence: 89%
See 4 more Smart Citations
“…To test lateral-line somatotopy functionally, we used a combination of pLAN map rewiring and a rheotaxis assay. In previous studies, we found that after peripheral nerve transection LANs regenerate axons to re-innervate neuromasts within 36 h 18,44 . Regenerating axons reproduce synapses with hair cells of the original planar polarization, recapitulating neuronal directional tuning 18,44 .…”
Section: Central-arbor Structure and Plan Receptive Fieldmentioning
confidence: 89%
“…In previous studies, we found that after peripheral nerve transection LANs regenerate axons to re-innervate neuromasts within 36 h 18,44 . Regenerating axons reproduce synapses with hair cells of the original planar polarization, recapitulating neuronal directional tuning 18,44 . However, they nearly always re-innervate a neuromast different from the original with a strong bias toward more caudal neuromasts, which strongly disrupts lateralis somatotopy 18 .…”
Section: Central-arbor Structure and Plan Receptive Fieldmentioning
confidence: 89%
See 3 more Smart Citations